2018
DOI: 10.1145/3161201
|View full text |Cite
|
Sign up to set email alerts
|

An LSTM Based System for Prediction of Human Activities with Durations

Abstract: Human activity prediction is an interesting problem with a wide variety of applications like intelligent virtual assistants, contextual marketing, etc. One formulation of this problem is jointly predicting human activities (viz. eating, commuting, etc.) with associated durations. Herein a deep learning system is proposed for this problem. Given a sequence of past activities and durations, the system estimates the probabilities for future activities and their durations. Two distinct Long-Short Term Memory (LSTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Our deep learning approach takes the time-frequency spectra of the PPG- and accelerometer-signals as input, and provides the estimated heart rate as output. Deep learning has already been applied to various time-series signals, such as for human activity recognition [20,21,22] or gait parameter extraction [23]. Gjoreski et al [24] compared deep and classical machine learning methods on the task of human activity classification, and showed that with sufficient data a convolutional neural network (CNN) outperforms classical models.…”
Section: Introductionmentioning
confidence: 99%
“…Our deep learning approach takes the time-frequency spectra of the PPG- and accelerometer-signals as input, and provides the estimated heart rate as output. Deep learning has already been applied to various time-series signals, such as for human activity recognition [20,21,22] or gait parameter extraction [23]. Gjoreski et al [24] compared deep and classical machine learning methods on the task of human activity classification, and showed that with sufficient data a convolutional neural network (CNN) outperforms classical models.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of deep learning for human activity recognition has become more prevalent [11,17,34,35]. Convolutional neural networks have been commonly used [21,34,37,62,63] due to their ability to capture spatial relationships between sensor signals.…”
Section: Human Activity Recognitionmentioning
confidence: 99%
“…Zhou et al [94] use the Fast-Slow layer for very short sessions and an attention layer for noisy sessions to predict the Dwell Time of the next user action. Krishna et al [36] and Zhou et al [94] predict the next action and its duration, which can be used to propose more interesting actions to the customer. Jing and Smola [31] model RNNs using Long-Short Term Memory cells to estimate when the user will return to a site and what will be their future interest.…”
Section: Interaction Time and Dwell Timementioning
confidence: 99%